A spectroscopic and chemometric study of virgin olive oils subjected to thermal stress - Maggio, Ruben Mariano (2011)
The paper describes a study of thermal stress of three different samples of virgin olive oil in terms of oxidative stability. Fatty acid composition, evaluation of oxidative stability under forced conditions (OSI), determination of UV-spectrophotometric oxidation indexes (k232 and k270) and spectral properties were explored along the thermal treatment. The samples were subjected to heating treatment at 180 °C and evaluated after 0, 30, 60, 90, 120, 150 and 180 min. Middle infrared (MIR) and visible-near infrared (Vis-NIR) spectra were elaborated by partial least squares modelling to individualise regions and bands where critical variations were present. Two bands were found as principal influential ones (1245-1180 cm-1 and 1150-1030 cm-1) on MIR while one primary region was identified on Vis-NIR (2200-1325 cm-1).